Conhecimento, uso e aceitabilidade do Tratamento Restaurador Atraumático (ART) por cirurgiões-dentistas da atenção básica - Madastavicius, Sheila Cristina Leite (2021)
This study is part of the research line “Management of Care, Work and Education in Health” of the Postgraduate Program in Clinical Management at the Federal University of São Carlos (UFSCar), São Carlos-Brazil. Because of the intrinsic relationship between this Professional Masters’ project with health policies, this research investigated the knowledge and opinions of dentists working in Primary Care in the city of São Carlos on Atraumatic Restorative Treatment (ART) and the receptivity of these professionals to use the strategy in the public service. This is an exploratory, observational, cross-sectional, and institutional study, based on a study population of 50 dentists, which corresponds to the total number of professionals working in primary care in the municipal network, 41 of whom answered the questionnaire. The variables herein investigated involved the following: general characteristics of the participants, their knowledge, suggestions, and materials used in the ART technique; intended use and actual use of ART in the public service; and potential barriers of not applying the ART technique, such as: operator’s opinion; operator’s opinion about the patient’s perception; workload; material support; clinical expertise for ART; supervision of the oral health service; oral health assistant. Descriptive analyses were performed on the following data: characterization of the participating professionals, frequency of responses, and comparison with their expected response, as well as associations between the usage and intended use variables and other variables of all blocks using the chi-square test or Fisher's Exact Test (significance value < 0.05). Regarding the general characteristics of the participants, 80.49% graduated before 1995 and 58.54% had more than 25 years of experience in public service. Regarding knowledge of the researched individuals, their suggestions, and the material used in the ART technique, it was noteworthy that 46.34% of the individuals understood it to be a type of provisional intervention or the same as the suitability of the environment; when analyzing the uses and intended application of the ART technique, 90.24% believed this strategy interrupts the process of caries and prevents the loss of the dental element and 70.73% agreed that it should be widely used in Primary Care. Concerning the barriers to not applying the technique, 46.34% of the participants considered it to be an inferior treatment when compared to other restorative techniques and only 39.02% indicated that the manager understands the concept of ART. In view of these findings and given the need for non-invasive procedures in oral health care services due to the arrival of the COVID-19 pandemic, a proposal for ART training for dentists in primary care in São Carlos-SP will be developed in collaboration with the Oral Health Coordination of the city administration.